Library technology and user services ; Planning, integration, and usability engineering - Chow, Anthony (Chandos information professional series., 2011)
Written as a technology guide for students, practitioners, and administrators, the focus of this book is on introducing current and future trends in library technology and automation within the larger context of strategic and systems planning, implementation, and continuous improvement. Technology is an essential resource for attaining both organizational and patron goals, and planning needs to emphasize the alignment between the clearly defined goals of each. For this alignment to occur on a consistent basis goals must be designed, or engineered, in a systematic fashion where technology fulfi.